Japan's Medium : and Long-Term Fiscal Challenges - Okamura, K. (IMF Working Papers; Working Paper ;, 1996)
This paper assesses the sustainability of Japan's fiscal position. The simulations indicate that, even if the government's pension reform plan is fully implemented, the initial budget imbalance, combined with pressures from population aging, would lead to explosive increases in government deficits and debt. Present-value calculations point to a fiscal 'gap' of about 4 percent of GDP, indicating the combination of tax increases and/or spending cuts that would be required to generate a sustainable long-run fiscal position. Finally, the paper presents an illustrative package of tax and spending measures that could be implemented to close this gap.